FAPbI3 perovskite solar cell and preparation method and application thereof
By adding hydroxyethyl methacrylate to the perovskite precursor solution to form a dense and smooth perovskite film, the defect density and surface roughness of traditional perovskite solar cell films is solved, and photovoltaic performance and preparation are improved The stability of the process is suitable for the development of flexible solar cells.
Patent Information
- Application Number
- CN202310708165.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-14
- Publication Date
- 2024-12-17
AI Technical Summary
The high defect density and rough surface of traditional FAPbI3 perovskite solar cell films lead to insufficient photovoltaic performance and stability, and the preparation process is complex and costly.
The grain boundary binder hydroxyethyl methacrylate is added to the perovskite precursor solution, and a dense and smooth perovskite film is formed by spin coating and annealing, reducing grain boundary defects and improving carrier mobility and crystallinity .
It significantly improves the photovoltaic performance and reproducibility of the preparation process of perovskite solar cells, enhances the flexibility of the film, and is suitable for the preparation of flexible solar cells.
Smart Images

Figure CN119156025A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of optoelectronic materials and devices, and in particular relates to a FAPbI3 perovskite solar cell and a preparation method and application thereof. Background Art
[0002] Due to the rapid growth of the global population and the rapid development of the economy, the demand for energy is increasing. The current mainstream energy is fossil energy, but this type of energy has a very long formation cycle and is non-renewable, and will eventually run out. So people began to focus on some renewable energy sources, and solar energy is the main focus. Solar energy is not only the most abundant clean energy on the earth, but is also considered to be the most likely energy to replace traditional fossil fuels.
[0003] In addition to the well-known collectors that directly utilize thermal radiation, there is also a solar cell for the use of solar energy. A solar cell is a device that converts sunlight into electricity, and crystalline silicon solar cells currently dominate commercial applications. However, it is well known that the manufacturing process of crystalline silicon solar cells is complicated, and the equipment used in the manufacturing process is expensive. Therefore, developing alternatives to crystalline silicon solar cells has become the goal of more and more scientific researchers. Among the many types of solar cells, perovskite solar cells stand out with their outstanding advantages. In just over a decade, the performance of perovskite solar cells has made great progress, and the photoelectric conversion efficiency has increased from the initial 3.9% to 25.7%.
[0004] The crystallinity of FAPbI3 thin films prepared by traditional methods and the photovoltaic performance and stability of the prepared devices still have room for improvement. The high defect density in FAPbI3 thin films is a capture site for carrier transport, which easily causes energy loss through non-radiative recombination, resulting in low efficiency and poor performance of the device. Although the crystallinity of the perovskite thin film prepared by continuous optimization by scientific researchers has been further enhanced, the surface of the prepared perovskite film is still uneven and rough, and the crystallinity is still not good enough, which is not conducive to the subsequent functional layer deposition and the preparation of high-performance perovskite solar cells. Therefore, it is particularly important to develop a perovskite solar cell with high energy conversion efficiency. Summary of the invention
[0005] In view of the above-mentioned shortcomings, the object of the present invention is to provide a FAPbI3 perovskite solar cell and its preparation method and application. The present invention reduces the roughness of the perovskite film by adding hydroxyethyl methacrylate, a grain boundary adhesive, to the perovskite precursor solution, thereby preparing a perovskite film with a dense and smooth morphology, and the perovskite device prepared based on the perovskite film has better photovoltaic performance.
[0006] To achieve the above object, the present invention is implemented through the following technical solutions:
[0007] A method for preparing a FAPbI3 perovskite solar cell comprises the following steps:
[0008] S1. Providing a conductive substrate;
[0009] S2. Preparing an electron transport layer on the conductive substrate;
[0010] S3. Preparing a perovskite layer on the electron transport layer, the perovskite layer comprising lead iodide, formamidine iodide and a grain boundary adhesive hydroxyethyl methacrylate;
[0011] S4. Preparing an interface modification layer on the perovskite layer;
[0012] S5. Preparing a hole transport layer on the interface modification layer;
[0013] S6. Vacuum-evaporating a metal intercalation layer and a metal electrode on the hole transport layer in sequence to obtain a FAPbI3 perovskite solar cell.
[0014] The present invention introduces hydroxyethyl methacrylate as a grain boundary adhesive into the perovskite layer. The hydroxyethyl methacrylate can be solidified during the annealing process of the perovskite film and distributed at the perovskite grain boundaries to play a role in bonding the grain boundaries, thereby reducing the grain boundary defects of the perovskite film and promoting the carrier mobility and crystallinity of the perovskite layer, thereby improving the photoelectric conversion efficiency of the device.
[0015] Preferably, in step S3, the method for preparing a perovskite layer on the electron transport layer comprises:
[0016] Lead iodide, formamidine iodide and hydroxyethyl methacrylate are mixed to prepare a precursor solution;
[0017] Under anhydrous and oxygen-free conditions, the precursor solution is spin-coated on the surface of the electron transport layer, and anti-solvent ether is added dropwise during the spin-coating process, followed by annealing to obtain the perovskite layer.
[0018] Preferably, the method for preparing the precursor solution comprises:
[0019] Dissolving lead iodide and formamidine iodide in a solvent at a molar ratio of 1:1 to obtain a mixed solution;
[0020] Hydroxyethyl methacrylate is added to the mixed solution to obtain the precursor solution.
[0021] Preferably, the solvent is a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide.
[0022] Preferably, the concentration of the mixed solution is 1.5 mmol / mL, and the added amount of the hydroxyethyl methacrylate accounts for 10% to 50% of the volume of the mixed solution.
[0023] Preferably, the added amount of the hydroxyethyl methacrylate accounts for 20% of the volume of the mixed solution.
[0024] Preferably, in the step of spin coating the precursor solution on the surface of the electron transport layer, the spin coating conditions are: first spin coating at a rotation speed of 1000 rpm for 10 seconds, then spin coating at a rotation speed of 5000 rpm for 10 seconds, then dropwise adding ether, and continuing to spin coating for 20 seconds.
[0025] Preferably, in the step of spin coating the precursor solution on the surface of the electron transport layer, the annealing temperature is 100 to 140° C., and the annealing time is 15 to 60 min.
[0026] The present invention also provides a FAPbI3 perovskite solar cell prepared by the above preparation method.
[0027] The third aspect of the present invention provides an application of the above-mentioned FAPbI3 perovskite solar cell in the optoelectronic field.
[0028] The beneficial effects of the present invention are:
[0029] The present invention helps to repair the perovskite film by adding a grain boundary adhesive hydroxyethyl methacrylate into the perovskite solution, making the perovskite film smoother and flatter, promoting the carrier mobility and crystallinity of the perovskite layer, thereby improving the photovoltaic performance of the device; and is beneficial to improving the flexibility of the perovskite film, and is expected to be used in the preparation of flexible perovskite solar cells.
[0030] The present invention adjusts the amount of hydroxyethyl methacrylate added as a grain boundary adhesive to change the concentration of the perovskite precursor solution, thereby regulating the crystallinity and density of the perovskite film, improving the quality of the FAPbI3 perovskite film, and simultaneously improving the photovoltaic performance of the device and the repeatability of the preparation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the drawings of the embodiment are briefly introduced below.
[0032] Figure 1 This is a schematic diagram of the structure of a FAPbI3 perovskite solar cell provided by an embodiment of the present invention;
[0033] Figure 2 is a graph showing the ultraviolet absorption of the perovskite film in Example 2;
[0034] Figure 3is an X-ray diffraction pattern of the perovskite film in Example 2;
[0035] Figure 4 It is the scanning electron microscope image of the perovskite film of comparative example 1 and embodiment 2. DETAILED DESCRIPTION
[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] An embodiment of the present invention provides a method for preparing a FAPbI3 perovskite solar cell, comprising the following steps:
[0038] S1. Providing a conductive substrate;
[0039] S2. Preparing an electron transport layer on the conductive substrate;
[0040] S3. Preparing a perovskite layer on the electron transport layer, the perovskite layer comprising lead iodide, formamidine iodide and a grain boundary adhesive hydroxyethyl methacrylate;
[0041] S4. Preparing an interface modification layer on the perovskite layer;
[0042] S5. Preparing a hole transport layer on the interface modification layer;
[0043] S6. Vacuum-evaporating a metal intercalation layer and a metal electrode on the hole transport layer in sequence to obtain a FAPbI3 perovskite solar cell.
[0044] In one embodiment, the conductive substrate in step S1 may be, but is not limited to, an ITO substrate or a FTO substrate.
[0045] In one embodiment, the electron transport layer in step S2 is SnO2, and the preparation steps are: spin coating SnO2 on the surface of the conductive substrate, the spin coating conditions are 4000 rpm for 30 seconds, and annealing at 150° C. for 30 minutes after spin coating.
[0046] In one embodiment, in step S3, the method for preparing a perovskite layer on the electron transport layer comprises:
[0047] Lead iodide and formamidine iodide are dissolved in a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide at a molar ratio of 1:1, and after complete dissolution, a mixed solution with a concentration of 1.5 mmol / mL is obtained, and then 10% to 50% of hydroxyethyl methacrylate by volume of the mixed solution is added to the mixed solution to prepare a precursor solution;
[0048] Under anhydrous and oxygen-free conditions, the precursor solution is spin-coated on the surface of the electron transport layer, and anti-solvent ether is added dropwise during the spin-coating process, followed by annealing to obtain the perovskite layer.
[0049] In one embodiment, the conditions for spin coating the precursor solution on the surface of the electron transport layer are: first spin coating at a rotation speed of 1000 rpm for 10 seconds, then spin coating at a rotation speed of 5000 rpm for 10 seconds, start adding ether, and then continue spin coating for 20 seconds; the annealing temperature is 100-140°C, and the annealing time is 15-60 minutes.
[0050] In one embodiment, the interface modification layer in step S4 is octyl ammonium iodide, and the preparation steps are: spin coating an isopropanol solution of octyl ammonium iodide with a concentration of 5 mg / mL on the perovskite layer, the spin coating conditions are 4000 rpm for 30 seconds, and then annealing at 100°C for 1 minute.
[0051] In one embodiment, the hole transport layer in step S5 is Spiro-OMeTAD, and the preparation steps are:
[0052] Dissolve Spiro-OMeTAD in chlorobenzene;
[0053] Dissolving lithium bis(trifluoromethanesulfonyl)imide in an acetonitrile solution to obtain a lithium salt solution;
[0054] Take 4-tert-butylpyridine (TBP) solution and add it to the Spiro-OMeTAD solution;
[0055] Adding the lithium salt solution to the Spiro-OMeTAD solution to obtain a Spiro-OMeTAD mixed solution;
[0056] The Spiro-OMeTAD mixed solution was spin-coated on the surface of the interface modification layer at 2500 rpm for 30 seconds.
[0057] In one embodiment, the metal intercalation layer in step S6 is MoO3, the metal electrode is Ag, and the preparation steps are:
[0058] MoO3 was vacuum-deposited on the hole transport layer at a rate of 0.2 Å / s and a thickness of 220 Å;
[0059] A metal Ag electrode was vacuum evaporated on MoO3 at a rate of 2 angstroms / second and a thickness of 2000 angstroms.
[0060] The present invention will be further described below by means of specific examples.
[0061] The laboratory temperature during the preparation of the following examples was approximately 20°C.
[0062] Example 1
[0063] This embodiment provides a method for preparing a FAPbI3 perovskite solar cell using a grain boundary adhesive, comprising the following steps:
[0064] Step 1) The etched FTO conductive glass with a size of 1.2×1.2 was ultrasonically treated in ethanol, ultrapure water with a cleaning agent, ultrapure water, and ethanol for 30 minutes each, and then dried with a nitrogen gun to obtain a clean FTO substrate.
[0065] Step 2) The FTO substrate cleaned in step 1) is treated with an ultraviolet ozone cleaning machine for 20 minutes.
[0066] Step 3) Take 40 μL of the diluted SnO2 solution and drop it onto the FTO substrate treated in step 2), and use a coating machine to spin coat it into a film. The spin coating conditions are 5000 rpm for 30 seconds, and then anneal at 150°C for 30 minutes to form a SnO2 electron transport layer.
[0067] Step 4) The FTO substrate on which the electron transport material is deposited in step 3) is treated with an ultraviolet ozone cleaner for 20 minutes.
[0068] Step 5) Weigh 0.8150g of lead iodide, 0.2648g of formamidine iodide and 0.03713g of methylamine chloride and dissolve them in 1000μL of a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide (volume ratio is 890μL:110μL), and stir on a cold table for 4-6 hours to completely dissolve them. Then take 100μL of hydroxyethyl methacrylate and add it to the completely dissolved perovskite solution, continue stirring for 24h, prepare a perovskite precursor solution, and select an organic filter membrane to filter the perovskite precursor solution.
[0069] Step 6) Place the FTO substrate with the electron transport layer deposited in step 4) on a coater, then drop 45 μL of the perovskite precursor solution on it, and use a two-step spin coating method for spin coating, specifically: first spin coating at 1000 rpm for 10 seconds, then spin coating at 5000 rpm for 30 seconds, and in the remaining 20 seconds, add 800 μL of ether. After spin coating, anneal at 140°C for 15 minutes to form a uniform and dense perovskite film.
[0070] Step 7) Under room temperature conditions, prepare an isopropanol solution of octyl ammonium iodide with a concentration of 5 mg / mL to obtain an OAI solution; add 40 μL of the OAI solution to the perovskite film prepared in step 6), then spin coat at 4000 rpm for 30 seconds, and then anneal at 100° C. for 1 minute to form an octyl ammonium iodide (OAI) interface layer.
[0071] Step 8) Dissolve 73.2 mg of Spiro-OMeTAD in 1 mL of chlorobenzene; dissolve 520 mg of lithium bis(trifluoromethanesulfonyl)amide in 1 mL of acetonitrile solution to prepare a lithium salt solution; add 28.8 μL of TBP solution to the Spiro-OMeTAD solution; add 17.6 μL of lithium salt solution to the Spiro-OMeTAD solution, and stir the mixed solution at room temperature for 2 hours to obtain a Spiro-OMeTAD mixed solution; add 50 μL of the Spiro-OMeTAD mixed solution to the OAI interface layer prepared in step 7), then spin coat at 2500 rpm / s for 30 seconds, and oxidize the coated film in an air glove box for 20 hours to form a hole transport layer.
[0072] Step 9) First, on the hole transport layer prepared in step 8), vacuum evaporate the metal intercalation layer MoO3 at a rate of 0.2 angstroms / second to a thickness of 220 angstroms; then, on the MoO3 layer, evaporate the metal Ag electrode at a rate of 2 angstroms / second to a thickness of 2000 angstroms to prepare a FAPbI3 perovskite solar cell.
[0073] Example 2
[0074] This embodiment is to prepare FAPbI3 perovskite solar cells using grain boundary adhesives, which is basically the same as Example 1, except that: in step 5), the amount of hydroxyethyl methacrylate added is 200 μL.
[0075] Figure 2 The ultraviolet absorption curve of the perovskite film prepared in Example 2 shows that an obvious absorption band edge appears at 772 nm, indicating that a perovskite film with good crystallinity has been successfully prepared; Figure 3 This is the X-ray diffraction diagram of the perovskite film prepared in this example. It can be seen that an α-FAPbI3 perovskite film is prepared.
[0076] Example 3
[0077] This embodiment is to prepare FAPbI3 perovskite solar cells using grain boundary adhesives, which is basically the same as Example 1, except that: in step 5), the amount of hydroxyethyl methacrylate added is 300 μL.
[0078] Example 4
[0079] This embodiment is to prepare FAPbI3 perovskite solar cells using grain boundary adhesives, which is basically the same as Example 1, except that: in step 5), the amount of hydroxyethyl methacrylate added is 400 μL.
[0080] Example 5
[0081] This embodiment is to prepare FAPbI3 perovskite solar cells using grain boundary adhesives, which is basically the same as Example 1, except that: in step 5), the amount of hydroxyethyl methacrylate added is 500 μL.
[0082] Comparative Example 1
[0083] The method for preparing the FAPbI3 perovskite film in this comparative example is basically the same as that in Example 1, except that hydroxyethyl methacrylate is not added in step 5).
[0084] Under standard test conditions (AM1.5G illumination), the photovoltaic performance of Examples 1 to 5 and Comparative Example 1 was tested, and the results are shown in Table 1 below.
[0085] Table 1 Photoelectric performance of perovskite solar cells prepared in various embodiments and comparative examples
[0086] performance Voc(V) <![CDATA[Jsc(mA / cm 2 )]]> FF(%) Efficiency(%) Example 1 1.07 24.54 82.06 21.69 Example 2 1.09 25.49 81.64 22.88 Example 3 1.10 23.96 81.93 21.76 Example 4 1.07 24.27 80.49 20.85 Example 5 1.08 23.71 79.66 20.52 Comparative Example 1 1.09 24.82 80.18 21.73
[0087] It can be seen from Table 1 that the perovskite solar cell prepared by using the grain boundary adhesive hydroxyethyl methacrylate in the present invention has a photovoltaic performance comparable to or even higher than that of Comparative Example 1.
[0088] It can be seen from Examples 1 to 5 that with the increase in the amount of hydroxyethyl methacrylate added, the photoelectric performance of the prepared device shows a trend of first increasing and then decreasing. This is because the addition of excessive hydroxyethyl methacrylate causes the perovskite precursor solution to be over-diluted, which in turn leads to a reduction in the thickness of the perovskite film and a reduction in the amount of photogenerated carriers generated, thereby affecting the photocurrent of the device and the efficiency of the entire device. In Example 2, since the amount of hydroxyethyl methacrylate added does not over-dilute the concentration of the perovskite precursor solution, the perovskite film prepared is of better quality, has the advantages of crystallinity and a smoother film, and the photovoltaic performance of the perovskite device is higher than that of the comparison example, indicating that without over-diluting the perovskite precursor solution, the grain boundary adhesive hydroxyethyl methacrylate can improve the crystallization performance of the perovskite, thereby preparing a device with better performance.
[0089] Although the photovoltaic performance of the FAPbI3 perovskite solar cells prepared in Examples 4 to 5 is slightly lower than that of the control example, it still has an efficiency of more than 20% when the perovskite solution is over-diluted, resulting in uneven film thickness and poor quality. This also confirms that hydroxyethyl methacrylate has the advantage of being able to improve the quality of the perovskite film and thus improve the photovoltaic performance of the device.
[0090] Figure 4 The scanning electron microscope images of the perovskite films prepared in Example 2 and Comparative Example 1 show that the perovskite film in the comparative example exhibits a large roughness, and the film is somewhat uneven, while the perovskite film in Example 2 has a relatively smooth and flat surface. This indicates that the FAPbI3 perovskite film prepared by adding a grain boundary adhesive in the present invention is solidified after annealing, and is distributed at the perovskite grain boundaries, playing a role in bonding the grain boundaries, so that the prepared perovskite film has fewer grain boundary defects.
[0091] It should be noted that the above embodiments all belong to the same inventive concept, and the description of each embodiment has its own focus. For matters that are not described in detail in some embodiments, reference may be made to the description in other embodiments.
[0092] The above-mentioned embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a FAPbI3 perovskite solar cell, characterized in that: The following steps are involved: S1. Providing a conductive substrate; S2. Preparing an electron transport layer on the conductive substrate; S3. Preparing a perovskite layer on the electron transport layer, the perovskite layer comprising lead iodide, formamidine iodide and hydroxyethyl methacrylate; S4. Preparing an interface modification layer on the perovskite layer; S5. Preparing a hole transport layer on the interface modification layer; S6. Vacuum-evaporating a metal intercalation layer and a metal electrode on the hole transport layer in sequence to obtain a FAPbI3 perovskite solar cell.
2. The method for preparing a FAPbI3 perovskite solar cell according to claim 1, characterized in that: In step S3, the method for preparing a perovskite layer on the electron transport layer comprises: Lead iodide, formamidine iodide and hydroxyethyl methacrylate are mixed to prepare a precursor solution; Under anhydrous and oxygen-free conditions, the precursor solution is spin-coated on the surface of the electron transport layer, and ether is added dropwise during the spin-coating process, followed by annealing to obtain the perovskite layer.
3. The method for preparing a FAPbI3 perovskite solar cell according to claim 2, characterized in that: The method for preparing the precursor solution comprises: Dissolving lead iodide and formamidine iodide in a solvent at a molar ratio of 1:1 to obtain a mixed solution; Hydroxyethyl methacrylate is added to the mixed solution to obtain the precursor solution.
4. The method for preparing a FAPbI3 perovskite solar cell according to claim 3, characterized in that: In the preparation of the precursor solution, the solvent is a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide.
5. The method for preparing a FAPbI3 perovskite solar cell according to claim 3, characterized in that: In the preparation of the precursor solution, the concentration of the mixed solution is 1.5 mmol / mL, and the added amount of the hydroxyethyl methacrylate accounts for 10% to 50% of the volume of the mixed solution.
6. The method for preparing a FAPbI3 perovskite solar cell according to claim 5, characterized in that: The added amount of the hydroxyethyl methacrylate accounts for 20% of the volume of the mixed solution.
7. The method for preparing a FAPbI3 perovskite solar cell according to claim 2, characterized in that: In the step of spin coating the precursor solution on the surface of the electron transport layer, the spin coating conditions are: first spin coating at a rotation speed of 1000 rpm for 10 seconds, then spin coating at a rotation speed of 5000 rpm for 10 seconds, then dropwise adding ether, and continuing to spin coating for 20 seconds.
8. The method for preparing a FAPbI3 perovskite solar cell according to claim 2, characterized in that: In the step of spin coating the precursor solution on the surface of the electron transport layer, the annealing temperature is 100 to 140° C. and the annealing time is 15 to 60 minutes.
9. A FAPbI3 perovskite solar cell prepared according to the preparation method according to any one of claims 1 to 8.
10. Application of the FAPbI3 perovskite solar cell according to claim 9 in the field of optoelectronics.
Citation Information
Patent Citations
Method for preparing FAPbI3 perovskite thin film and efficient perovskite solar cell by using FAPbI3 perovskite thin film
CN114678472A
Method for preparing high-efficiency flexible perovskite solar cell through buried interface treatment
CN114695667A
Preparation method of high-quality and high-stability perovskite layer and solar cell
CN114899324A
Method for preparing passivation layer of perovskite battery and application
CN115568268A
2D-3D high-stability perovskite solar cell and preparation method thereof
CN115988886A
Cited By
Perovskite thin film constructed in situ based on thermal initiation fluorinated polymerization grid, and preparation method and application thereof
CN121127094A
